Harmoni dalam Penderitaan: Pemahaman Teodisi melalui Roma 8:28 dalam Kehidupan Rohani Jemaat - Purwonugroho, Daniel Pesah (Pusat Studi Pentakosta Indonesia, 2024)
AbstractThis paper aims to explore the harmony within suffering through the understanding of theodicy from the perspective of Romans 8:28 for the spiritual life of the congregation. Theodicy is a concept that reconciles the existence of a benevolent God with the suffering and hardships faced by humanity. Theodicy can also be understood and explored through the Bible. Romans 8:28 provides a framework of thinking about theodicy that benefits the spiritual life of the congregation. Romans 8:28 affirms God's involvement in various human situations and conditions to bring about positive outcomes in human life. Theodicy from the perspective of Romans 8:28 can have both theological and practical implications for the life of the congregation. Through a qualitative descriptive approach, the author seeks to explore the understanding of theodicy through Romans 8:28 and its correlation with the spiritual life of the congregation. The author asserts that understanding theodicy through Romans 8:28 will bring about a harmony in suffering that has a significant impact on the spiritual life of the congregation.Keywords: Harmony, Suffering, Theodicy, Romans 8:28AbstrakTulisan ini dirangkai untuk mengeksplorasi harmoni di dalam penderitaan melalui pemahaman teodisi dalam perspektif Roma 8:28 bagi kehidupan rohani jemaat. Teodisi merupakan konsep yang mendamaikan eksistensi Allah yang baik di dalam penderitaan dan masa sukar yang dihadapi oleh manusia. Teodisi juga dapat dipahami dan dieksplorasi melalui Alkitab. Roma 8:28 memberikan kerangkan berpikir tentang teodisi yang memberikan manfaat bagi kehidupan rohani jemaat. Roma 8:28 menegaskan tentang Allah yang terlibat di dalam berbagai macam situasi dan kondisi manusia untuk memberikan keuntungan yang positif dalam kehidupan manusia. Teodisi dalam perspektif Roma 8:28 dapat memberikan implikasi baik secara teologis maupun secara praktis di dalam kehidupan jemaat. Melalui pendekatan kualitatif deskriptif, penulis mencoba untuk menjelajahi pemahaman teodisi melalui Roma 8:28 dan korelasinya bagi kehidupan rohani jemaat. Penulis menegaskan bahwa pemahaman teodisi melalui Roma 8:28 akan mendatangkan sebuah harmoni dalam penderitaan yang berdampak signifikan dalam kehidupan rohani jemaat.Kata kunci : Harmoni, Penderitaan, Teodisi, Roma 8:28